THE EFFECT OF WORD MAPPING TECHNIQUE ON STUDENTS’ VOCABULARY MASTERY - Irma Fatihatul Hidayah (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
ABSTRACT : Vocabulary plays an important role as the main component to make the language being understandable and creates an effective communication in English. In learning process, students usually do not recognize many words that hinders them in understanding the language whether spoken or written language. Meanwhile, teachers also face some problems frequently, such as they do not know the right way how to teach vocabulary, or they use uninteresting technique which makes students bored during the learning process. Therefore, as a necessary tool that affects every skill, vocabulary should be mastered to help students comprehend the language well, while teacher is expected to have an appropriate technique in teaching vocabulary.            The aim of this study was to know whether there is any significant effect of using word mapping on students’ vocabulary mastery. Quasi experimental method was used in order to find the result of this study. There were 40 students of 10th grader of MA Hidayatul Ulum, Lampung who became the population and also the sample of this study. In order to collect the data, the researcher used pre- test and post- test that consisted of 20 multiple choice questions for each test and analyzed them by using pre- requisite test (normality and homogeneity test) followed by independent T- test as the last step of data analysis.            The result of this study showed the significance value at 0.000 that was lower than 0.05. It means that there was significant effect of using word mapping on students’ vocabulary mastery. In other words, word mapping is a helpful technique that can be applied by teacher to assist the students in learning vocabulary.            Based on the result of this study, the researcher suggested that teacher can use word mapping as the vocabulary teaching technique matched with the material that will be taught in the class. Besides, further researchers are suggested to use word mapping in different level of research subject and use the different research design to find another result of the research. Key words: vocabulary, vocabulary mastery, word mapping